The Costs and Consequences of US Drones Warfare in Pakistan - Sawaira Rashid; Gulshan Majeed; Muhammad Ikram (ASIAN Journal of International Peace & Security (AJIPS), 2023)
This research delves into the multifaceted impacts of the United States’ drone warfare strategy in Pakistan. The study adopts a comprehensive approach to examine the various dimensions of this strategy, including its political, social, economic, and psychological consequences. Through an empirical analysis, the article scrutinizes the toll of drone strikes on both militant targets and civilian populations in Pakistan. It evaluates the effectiveness of drone warfare in achieving its intended objectives of eliminating terrorist threats while also considering the collateral damage and civilian casualties incurred. The study places a particular emphasis on the psychological and emotional ramifications experienced by Pakistani citizens living under the constant threat of drone attacks. Furthermore, the article assesses the diplomatic implications of the US drone warfare program in Pakistan. By focusing on Pakistan as a case study, this article contributes to the broader discourse on the ethical considerations, strategic efficacy, and unintended consequences of employing drone warfare as a counterterrorism tool. The study provides a more nuanced understanding of the complex interplay between security strategies, human rights, diplomacy, and the wellbeing of civilian populations in regions affected by drone warfare.